Early Alterations of Endothelial Nitric Oxide Synthase Expression Patterns in the Guinea Pig Cochlea After Noise Exposure. (November 2019) - Heinrich, Ulf R.; Schmidtmann, Irene; Meuser, Regina; Ernst, Benjamin P.; Wünsch, Desiree; Siemer, Svenja; Gribko, Alena; Stauber, Roland H.; Strieth, Sebastian
Constitutively expressed endothelial nitric oxide synthase (eNOS) is supposed to play a role in noise-induced nitric oxide (NO)-production. It is commonly known that intense noise exposure results in inducible NOS (iNOS) expression and increased NO-production, but knowledge about a contribution of the eNOS isoform is still lacking. Effects of noise exposure on eNOS immunolabeling were determined in male guinea pigs ( n =24). For light microscopic analysis, 11 animals were exposed to 90 dB for 1 hr and 6 animals were used as controls. After exposure, eNOS immunostaining was performed on paraffin sections, and the staining intensities were quantified for 4 cochlear regions. For electron microscopic analysis, 2 animals were exposed for 2 hr to 90 dB and 5 animals were used as controls. The intensity of eNOS immunolabeling was found to be already comprehensively increased 1 hr after noise exposure to 90 dB. At the ultrastructural level, a clear increase in eNOS immunolabeling was found in microtubules-rich areas of cochlear cuticular structures. Hence, our findings indicate that the reticular lamina forming the endolymph–perilymph barrier at the apical side of the organ of Corti is involved in a fast intrinsic otoprotective mechanism of the cochlea.